Patients' experiences and perceived causes of persisting discomfort following day surgery - Bergh Ingrid HE; Rosén Helena I; Lundman Berit M; Mårtensson Lena B (BMC, 2010)
Abstract Background The aim of this study was to describe patients' experiences and perceived causes of persisting discomfort following day surgery. Earlier research has mainly covered symptoms and signs during a recovery period of up to one month, and not dealt with patients' perceptions of what causes persisting, longer-term discomfort. Methods This study is a part from a study carried out during the period May 2006 to May 2007 with a total of 298 day surgery patients. Answers were completed by 118 patients at 48 hours, 110 at seven days and 46 at three months to one open-ended question related to discomfort after day surgery constructed as follows: If you are still experiencing discomfort related to the surgery, what is the reason, in your opinion? Data was processed, quantitatively and qualitatively. Descriptive, inferential, correlation and content analyses were performed. Results The results suggest that patients suffer from remaining discomfort e.g. pain and wound problem, with effects on daily life following day surgery up to three months. Among patients' perceptions of factors leading to discomfort may be wrongful or suboptimal treatment, type of surgery or insufficient access to provider/information. Conclusions The results have important implications for preventing and managing discomfort at home following day surgery, and for nursing interventions to help patients handle the recovery period better.